Transformasi Peran Organisasi Kepemudaan Dalam Pendidikan Politik: Studi Kasus Banteng Muda Indonesia di Provinsi Lampung - Nadya Mahamida; Sinta Bella Farah Kirani; Rozalia Rozalia; Teki Prasetyo; Ana Mentari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the transformation of youth organizations’ roles in political education in Indonesia, focusing on the Banteng Muda Indonesia (BMI) organization in Lampung Province. As the youth wing of the Indonesian Democratic Party of Struggle (PDI-P), BMI holds a crucial role in promoting political values, disseminating party ideology, and shaping the political awareness of the younger generation. The transformation of this role is significant to examine in light of the evolving political landscape, shifting preferences among youth, and new challenges in political communication influenced by social media and information technology. This research investigates how BMI Lampung has adjusted its approaches and strategies in political education over time. Previously, the organization's approach tended to be indoctrinative and top-down; however, it has gradually shifted towards a more participatory and dialogical model. In this new model, young cadres are empowered to engage actively in political discussions, leadership training, and community service activities. This transformation reflects not only internal organizational change but also an adaptive response to external factors such as increasing political apathy and declining public trust in political parties.